Optical properties of mineral dust outbreaks over the northeastern Mediterranean - Oguz, T; Cokacar, T; Kubilay, N (Journal of Geophysical Research: Atmospheres, 2003)
Ground-based aerosol optical measurements were conducted within the framework of the Aerosol Robotic Network (AERONET) program at the IMS-METU site at Erdemli (36degrees33'N, 34degrees15'E) along the Turkish coast of the northeastern Mediterranean from January 2000 to June 2001. The measurements were used to identify and define predominant regional aerosol optical properties, with an emphasis on mineral dust intrusion events. Dust storms affecting the region primarily originate from the central Sahara in spring, the eastern Sahara in summer, and the Middle East/Arabian peninsula in autumn. Summer and autumn dust intrusions usually occurred at higher altitudes (above 700 hPa), whereas urban-industrial aerosols from the north over the Balkan region, Ukraine, and Anatolia were transported to the region at lower altitudes. In addition to a drastic increase in the aerosol optical thickness, in some cases up to 1.8, the dust episodes were characterized by (1) a sharp drop in the Angstrom coefficient to values near zero, (2) a high-scattering with single-scattering albedo greater than 0.95+/-0.03, and the real part of the refractive index around 1.5+/-0.5, both of which acquire slightly higher values at longer wavelengths, (3) a lower absorption given by the imaginary part of the refractive index less than 0.002, and (4) an almost neutral spectral dependence of these parameters. Dust particles possessed a bimodal size distribution with typical volume mean radii of 2.2 mm and 0.08 mum for coarse and fine size fractions, respectively, and corresponding volume concentrations of about 1.0 and 0.1 mum(3) mum(-2) of dust particles. It was apparent that the Saharan and Middle East desert dusts differ in their absorption index values (0.0015 and 0.0005, respectively). The difference is likely a result of their contrasting mineralogies.